МИФОЛОГИЗМ ХХ АСР АДАБИЁТИНИНГ ЭНГ ХАРАКТЕРЛИ ҲОДИСАСИ - Жовлиев, Б. (SCIENCE and SOCIETY, 2018)
The article analyses the impact of various traditions and styles in the prosaic genre of world literature on the development of Uzbek national literature (prose). Based on the works of the writer Nazar Eshonkul it proves the absorption of leading mythological approaches, mythopoetic images and interpretations in the world literature of the 20th century into the national literature.